Research on the relationship between social capital and sustainable livelihood: evidences from reservoir migrants in the G Autonomous Prefecture, China - Zhang, Huashan; Cao, Zhijie; Zhou, Kexin; Ji, Yuanyuan (Frontiers in Environmental Science, 2024)
Although hydropower serves as a clean alternative energy source, the global challenge of resettlement due to dam construction underscores the importance of sustainable livelihoods in achieving the targets of the Sustainable Development Goals (SDGs). In recent years, the sustainable livelihood theory has offered a new perspective for examine the development of livelihoods of reservoir migrants after relocation. However, in-depth relationship between social capital and sustainable livelihoods has not been explored. In this study, three hydropower resettlement areas were selected in the G Autonomous Prefecture of China as an example. Our investigation delved into the influence of social networks, social norms, and social trust on the livelihoods of reservoir migrants. Study employed semi-structured interviews, participant observation, and qualitative analysis to explore this impact. The results show that the traditional social capital stock of reservoir migrants, dominated by family, neighborhood and religious networks, has declined. Therefore, the structural function of modern social capital should be strengthened by increasing the social trust of reservoir migrants in institutions and civil society organizations. The contribution of livelihood diversification in poverty reduction by 2030 (SDG-1) was realized by focusing on the role of social capital to promote infrastructure, improve living conditions and increase employment opportunities for migrants. The findings further point to the need to fully respect the customs and lifestyles of ethnic minorities during the resettlement process of reservoir migrants in order to preserve the role played by their traditional social capital, thereby promoting the sustainable development of the livelihoods of reservoir migrants.